2005
DOI: 10.1007/s00442-005-0074-8
|View full text |Cite
|
Sign up to set email alerts
|

Do lizards and snakes really differ in their ability to take large prey? A study of relative prey mass and feeding tactics in lizards

Abstract: Adaptations of snakes to overpower and ingest relatively large prey have attracted considerable research, whereas lizards generally are regarded as unable to subdue or ingest such large prey items. Our data challenge this assumption. On morphological grounds, most lizards lack the highly kinetic skulls that facilitate prey ingestion in macrostomate snakes, but (1) are capable of reducing large items into ingestible-sized pieces, and (2) have much larger heads relative to body length than do snakes. Thus, maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Amongst squamates, strike latency has been shown to be highly correlated with the size of the prey relative to size of the predator (Shine & Sun, 2003; Shine et al ., 2004a; Shine & Thomas, 2005) as well as predator T b (Van Damme et al ., 1991; Diaz, 1994), but not the level of hunger (Hayes, 1993). We found that strike latency in the hime‐habu was only correlated with predator T b , and not relative prey size (expressed as partial regression coefficients) or level of hunger .…”
Section: Discussionmentioning
confidence: 99%
“…Amongst squamates, strike latency has been shown to be highly correlated with the size of the prey relative to size of the predator (Shine & Sun, 2003; Shine et al ., 2004a; Shine & Thomas, 2005) as well as predator T b (Van Damme et al ., 1991; Diaz, 1994), but not the level of hunger (Hayes, 1993). We found that strike latency in the hime‐habu was only correlated with predator T b , and not relative prey size (expressed as partial regression coefficients) or level of hunger .…”
Section: Discussionmentioning
confidence: 99%
“…Optimal foraging theory hypothesizes that efficient foragers will be favoured by natural selection, with such predators making decisions that maximize their rate of energy intake while searching for food, a short‐term phenotypic measure of fitness (Godin & Keenleyside, ). The size (mass) of an ingested prey relative to the body size of its predator (relative prey mass, RPM), which is regarded as a central tenet of foraging ecology, varies both within and among species (Hughes, ; Shine & Thomas, ). Although dietary data for a foraging fish species can be obtained in various ways, gut content analysis is the only one that provides direct information on the sizes of the prey taxa ingested by that predator and, at the same time, enables the numbers, mass and volumes of those taxa to be recorded (Hyslop, ).…”
Section: Introductionmentioning
confidence: 99%
“…We quantify the extent of parallelism in available diet between these environments and if traits related to the ability to exploit food sources, including bite force, head shape, relative head size, and body size, also have diverged in parallel. These traits are ecologically important, as diet is known to influence bite force (Herrel et al 2001, Santana et al 2012, and head shape in lizards is closely linked to bite force and feeding muscles, and, thereby, the capacity to handle large and/ or tough prey items (Shine and Thomas 2005). Furthermore, relatively wider heads are known to give stronger bite force (Herrel et al 2005, Dumont et al 2009), providing a natural link between morphology, performance, and ecology.…”
Section: Introductionmentioning
confidence: 99%